2022
DOI: 10.1186/s12889-022-13978-0
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties and measurement invariance of the Burnout Assessment Tool (BAT-23) in South Africa

Abstract: Background Burnout is an increasing public health concern that afflicts employees globally. The measurement of burnout is not without criticism, specifically in the context of its operational definition as a syndrome, also recently designated as such by the World Health Organisation. The Burnout Assessment Tool (BAT-23) is a new measure for burnout that addresses many of the criticisms surrounding burnout scales. The aim of this study is to determine the validity, reliability, and measurement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…Correlation matrix for the Job Demands-Resources model.Furthermore, H 3a and H 3b were also supported as the BAT-12 was found to be invariant for both gender and ethnicity. This result is in line with the measurement invariance tests conducted for the BAT-23 within the South African context that showed strong measurement invariance for gender and ethnicity(De Beer et al, 2022) and other invariance tests that have shown the cross-cultural validity of theBAT (e.g. De Beer et al, 2020).…”
supporting
confidence: 86%
“…Correlation matrix for the Job Demands-Resources model.Furthermore, H 3a and H 3b were also supported as the BAT-12 was found to be invariant for both gender and ethnicity. This result is in line with the measurement invariance tests conducted for the BAT-23 within the South African context that showed strong measurement invariance for gender and ethnicity(De Beer et al, 2022) and other invariance tests that have shown the cross-cultural validity of theBAT (e.g. De Beer et al, 2020).…”
supporting
confidence: 86%
“…This assumption can also lead to inflated factor correlations. Instead, ESEM allows items to load on nontarget factors with target rotation close to zero (De Beer et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The MBI-GS is a valid and reliable tool to measure burnout, which has been used by researchers in South Africa in several studies with similar samples ( Peltzer et al, 2003 ; Thomas and Valli, 2006 ). A validation study in South Africa on the BAT ( De Beer et al, 2022 ) was underway during the times of this research, thus the preference of the MBI-GS. It was used in phase I to evaluate and measure the level of burnout objectively, which was the final criterion for selecting participants.…”
Section: Methodsmentioning
confidence: 99%